Personal perspective: in search of an optimum cycling posture - de Vey Mestdagh, K. (Applied Ergonomics, 1998)
Correct cycling posture improves performance and may prevent injuries. This article addresses the most important variables that determine cycling posture of road racing cyclists. It focuses not only on "posture height" but also on "posture length", an aspect that has as yet received little attention. In order to help cyclists find their optimum posture, reliable anthropometric measuring is of utmost importance. The relevant measurements and the necessary measuring instruments are considered. Special attention is given to gender related posture aspects.